2012
DOI: 10.2209/tdcpublication.53.17
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial Cysts of Oral Mucosa: Two Cases in Different Regions

Abstract: Lymphoepithelial cyst of the oral cavity is a rare cystic lesion that presents as an asymptomatic, well-circumscribed, yellowish small submucosal nodule covered by normal overlying mucosa, usually located in the floor of the mouth or in the ventral or posterolateral surface of the tongue. Histopathological examination reveals a cyst lined by a stratified squamous epithelium surrounded by lymphoid tissue. In this paper, we report two cases of oral lymphoepithelial cyst, one on the anterior floor of the mouth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 22 publications
(18 reference statements)
4
18
0
Order By: Relevance
“…The major histopathological description of OLEC is that of a cystic lesion lined by a parakeratinized squamous epithelium that has a flat interface with the cystic wall of fibrous connective tissue in which lymphocytic aggregates are found. The cystic lumen may contain a thick gelatinous whitish‐yellow liquid compatible with keratin, desquamated epithelial cells, and inflammatory cells . We confirm some of these features in the present study but with the following variations: a non‐keratinized epithelium predominated; epithelial hyperplasia was a common finding, blurring the clear separation between the cystic epithelium and the fibrous capsule; lymphoid follicles were not ubiquitously seen in the capsule; and many cases exhibited an evenly organized lymphocytic infiltrate.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The major histopathological description of OLEC is that of a cystic lesion lined by a parakeratinized squamous epithelium that has a flat interface with the cystic wall of fibrous connective tissue in which lymphocytic aggregates are found. The cystic lumen may contain a thick gelatinous whitish‐yellow liquid compatible with keratin, desquamated epithelial cells, and inflammatory cells . We confirm some of these features in the present study but with the following variations: a non‐keratinized epithelium predominated; epithelial hyperplasia was a common finding, blurring the clear separation between the cystic epithelium and the fibrous capsule; lymphoid follicles were not ubiquitously seen in the capsule; and many cases exhibited an evenly organized lymphocytic infiltrate.…”
Section: Discussionsupporting
confidence: 85%
“…The pathogenesis of OLEC remains an issue of debate, but two main theories are put forth. One suggests an origin from ectopic entrapped glandular epithelium in regions where lymphoid tissue is present and the other suggests either the obstruction of a tonsil crypt or traumatic epithelial implantation into deeper tissues …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have hypothesized that ectopic foci of embriologic epithelium become entrapped within lymphoid tissue and may proliferate to form a cyst (15). However, other authors have suggested that oral lymphoepithelial cysts are the result of obstruction of crypts of otherwise normal oral tonsils (13,15). It is also possible that traumatic implantation of epithelial cells into deeper tissues can lead to cyst formation (13).…”
Section: Discussionmentioning
confidence: 99%
“…This condition must be differentiated from lesions that appear as submucosal papules or nodules such as lipoma and mucoceles. Sialolithiases and minor salivary gland tumors must also be included in clinical differential diagnosis (8,13,15). Histopathologically, it presents as a central cystic lesion lined with stratified squamous epitelium surrounded by lymphoid tissue similar to the histopathological findings in cervical lymphoepithelial cyst (15).…”
Section: Discussionmentioning
confidence: 99%